Does everyone use probabilities? Intuitive and rational decisions about stockholding - Johannes Binswanger; Martin Salm (Institute for the Study of Labor (IZA), 2013)
We investigate the relationship between subjective probabilities of future stock market returns and decisions about stockholding. Specifically, we examine whether acting upon subjective probabilities is confined to individuals with high cognitive skills. We explore this question using data from the U.S. Health and Retirement Study (HRS). Our empirical analysis is guided by a novel and simple model based on the dual-systems framework from psychology (Kahneman, 2003). In our model, individuals with low cognitive skills make decisions in an intuitive non-probabilistic way based on cues and feelings. Individuals with high cognitive skills make decisions akin to the expected utility model. As predicted by our model, in our empirical analysis we find that there is a significantly stronger association between subjective return probabilities and stockholding decisions for individuals with high cognitive skills, compared to individuals with lower cognitive skills. The paper contributes to a better understanding of the role of cognitive skills in decision making under uncertainty.
Keywords: D03; D81; D84; G11; 330; subjective expectations; probabilities; dual system decision making; cognitive skills; cognitive economics